Hierarchy of Needs to Staff Performances that Affect to Employees Loyalty of Chengde Steel Logistics Co.,Ltd. - Liu , Jiajun; Kittimanorom, Prapatsorn (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2019)
The objective of this study was to investigate the hierarchy of needs to staff performances, to study employees' loyalty of Chengde Steel Logistics Co., Ltd., and to study the relationship of the hierarchy of needs to staff performances that employees Loyalty of Chengde Steel Logistics Co., Ltd. The research instrument was the questionnaire. Data collected were analyzed through frequency, percentage, mean, standard deviation and Pearson’s correlation coefficient. The sampling of this study was 223 individuals, those aged between 21-30 years, graduated with a bachelor’s degree, 31-40 years of the work period, and those with production staff. The analytic results of the hierarchy of needs to staff performances of Chengde Steel Logistics Co., Ltd, with mean score of 4.18 from highest to lowest mean scores as follows, the respondents had high, ate level, needs for Physiological, needs for Security or Safety needs, and need for esteem needs at low level respectively. In terms of Loyalty, overall the respondents had a moderate level, with a mean score of 3.42. The factors were ranked from highest to lowest mean scores as follows: affective aspect, behavioral aspect and cognitive aspect at low level respectively. The results of hypothesis testing showed that the Hierarchy of needs to staff performances positively related to the employee's loyalty to Chengde Steel Logistics Co., Ltd, was high related. The statistic significant was .05